Zinc and its transporters in epigenetics - Brito, Sofia; Lee, Mi Gi; Bin, Bum Ho; Lee, Jong Soo (Molecules and Cells, 2020)
Epigeneti c events li ke DNA methyl ati on and hi stone modification can alter heritable phenotypes. Zinc is required for the activity of various epigenetic enzymes, such as DNA methyltransferases (DNMTs), histone acetyltransferases (HATs), hi stone deacetyl ases (HDACs), and hi stone demethylases, which possess several zinc binding sites. Thus, the dysregulation of zinc homeostasis can lead to epigenetic alterations. Zinc homeostasis is regulated by Zinc Transporters (ZnTs), Zrt-and Irt-like proteins (ZIPs), and the zinc storage protein metallothionein (MT). Recent advances revealed that ZIPs modulate epigenetics. ZIP10 deficiency was found to result in reduced HATs, confirming its involvement in histone acetylation for rigid skin barrier formation. ZIP13 deficiency, which is associated with Spondylocheirodysplastic Ehlers– Danlos syndrome (SCD-EDS), increases DNMT activity, leading to dysgenesis of dermis via improper gene expressions. However, the precise molecular mechanisms remain to be elucidated. Future molecular studies investigating the involvement of zinc and its transporters in epigenetics are warranted.
Keywords: Cation Transport Proteins; Epigenesis, Genetic; Epigenomics; Humans; Zinc; Epigenetics; Zinc; Zinc transporter